Seasonal variations in macrophytic biomass in a shallow pond at Biratnagar, Nepal - Niroula, Bhabindra; Singh, K.L.B. (Nepalese Journal of Biosciences, 2013)
Macrophytic biomass in a shallow pond ranged between 82.8 - 1134.6 g/m2; 16.0 - 75.7 g/m2; 170.6 - 1600.1 g/m2 for emergent, submerged and free floating community, respectively. Maximum total community biomass (2725.2 g/m2) was recorded in August with major contribution of water hyacinth. During rainy season, total phosphate (PO4-P) - 0.17 mg/l; nitrate (NO3-N) - 0.7 mg/l; nitrite (NO2-N) - 0.02 mg/l and ammonia (NH3-N) - 5.2 mg/l; were maximum, whereas, pH (6.3), dissolved oxygen (6.3 mg/l) and conductivity (184 µs/cm); were minimum in water samples.